2012
DOI: 10.1016/j.jneumeth.2012.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of laser-induced heating in optical neuronal guidance

Abstract: a b s t r a c tRecently, it has been shown that it is possible to control the growth direction of neuronal growth cones by stimulation with weak laser light; an effect dubbed optical neuronal guidance. The effect exists for a broad range of laser wavelengths, spot sizes, spot intensities, optical intensity profiles and beam modulations, but it is unknown which biophysical mechanisms govern it. Based on thermodynamic modeling and simulation using published experimental parameters as input, we argue that the gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 47 publications
0
21
1
1
Order By: Relevance
“…It is known that calcium ions are an integral part of common signalling pathways and have been extensively studied for their role in cell responses such as mitosis, apoptosis, muscle contraction and neurite extension. 20,21 It is hypothesised that the recorded cytoplasmic Ca 2+ elevations caused by laser -exposed NRs might be correlated with the neurite outgrowth described in Ref. 10.…”
Section: Discussionmentioning
confidence: 94%
“…It is known that calcium ions are an integral part of common signalling pathways and have been extensively studied for their role in cell responses such as mitosis, apoptosis, muscle contraction and neurite extension. 20,21 It is hypothesised that the recorded cytoplasmic Ca 2+ elevations caused by laser -exposed NRs might be correlated with the neurite outgrowth described in Ref. 10.…”
Section: Discussionmentioning
confidence: 94%
“…Calcium ions play an important role in different cellular activities, such as mitosis, muscle contraction and neurite extension 25,26 . In response to a stimulus, Ca 2+ increases, oscillates and decreases, leading to the activation, modulation or termination of a specific cell function.…”
Section: Representative Resultsmentioning
confidence: 99%
“…Different groups have also demonstrated that small temperature gradients over the physiological temperature range can be used to induce other responses, such as neuronal growth cone guiding 25 or depolarizing currents in human embryonic kidney cells 35 . Yong and coworkers recorded a significant increase in electrical signal activity in primary auditory neurons cultured with silica-coated Au NRs after laser irradiation of the NRs at the LSPR.…”
Section: Discussionmentioning
confidence: 99%
“…It relies on local temperature elevations caused by infrared light to functionally stimulate excitable cells to depolarise. Several papers have been published showing that infrared light can be used as a stimulus to excite neurons, cardiac myocytes as well as to act as a cue for guiding cell growth [12][13][14][15]. In addition to neural activation, neural inhibition has also been reported [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%